The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fphar.2022.930614
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis induced by iron overload promotes fibrosis in ovarian endometriosis and is related to subpopulations of endometrial stromal cells

Abstract: Endometriosis (EMs) is defined as the presence of tissue somewhat resembling endometrial glands and stroma outside the uterus; the retrograded endometrium grows in the peritoneal cavity and elicits fibrosis. Ferroptosis is a recently discovered form of programmed cell death, which is iron-dependent. The induction of ferroptosis has been found to participate in fibrosis. However, the relationship between EMs fibrosis and ferroptosis remains unknown. In this study, we confirmed that the iron content in ectopic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Large amounts of this trace element have been detected not only in ectopic lesions [ 105 , 113 , 114 ] but also in peritoneal fluid [ 115 ], follicular fluid [ 91 , 116 , 117 ], and blood [ 118 ] collected from patients with endometriosis. Additionally, suggestions indicating the involvement of Fe in the malignant transformation of OMA [ 119 ], dysmenorrhea [ 120 ], or the formation of adhesions [ 121 ] further emphasize the important role of Fe in the pathogenesis of endometriosis. Unfortunately, despite such an important role of Fe in the course of endometriosis and numerous studies assessing its impact on the development of the disease, no reports link Fe with diet.…”
Section: The Role Of Selected Dietary Components In the Course Of End...mentioning
confidence: 99%
“…Large amounts of this trace element have been detected not only in ectopic lesions [ 105 , 113 , 114 ] but also in peritoneal fluid [ 115 ], follicular fluid [ 91 , 116 , 117 ], and blood [ 118 ] collected from patients with endometriosis. Additionally, suggestions indicating the involvement of Fe in the malignant transformation of OMA [ 119 ], dysmenorrhea [ 120 ], or the formation of adhesions [ 121 ] further emphasize the important role of Fe in the pathogenesis of endometriosis. Unfortunately, despite such an important role of Fe in the course of endometriosis and numerous studies assessing its impact on the development of the disease, no reports link Fe with diet.…”
Section: The Role Of Selected Dietary Components In the Course Of End...mentioning
confidence: 99%
“… 55 Research on the mechanism of ferroptosis has focused on the effects of oxidative damage, the direction of iron metabolism regulation, and related targets. 47 , 56 Studies have shown that cell sensitivity to ferroptosis can be changed by regulating the intracellular iron content, and the combination of ferroptosis therapy with radiotherapy, chemotherapy, and targeted therapy for gastric cancer has shown good therapeutic effects in vivo and in vitro. 16 , 57 , 58 Identifying the downstream signal transduction or iron-dependent ROS production pathways using specific indicators would further clarify the ferroptosis mechanism and distinguish ferroptosis from other types of cell death, which has recently become a research focus, and the ferroptosis mechanism can be distinguished from other mechanisms involved in iron metabolism, oxidative damage, and other diseases-related processes to suggest new research ideas and treatment, which shows important clinical significance.…”
Section: Problems and Perspectivesmentioning
confidence: 99%
“…On the other hand, ferroptotic endometrial stromal cells can release inflammatory cytokines and activate downstream regulatory pathways to promote proliferation and angiogenesis in surrounding tissues. Iron overload in ectopic endometrial stromal tissues from patients with ovarian endometriosis-induced ferroptosis, which promoted fibrosis and tissue adhesions, and the process was associated with endometrial stromal cell subpopulations [ 106 ]. In a recent study, Li et al found that ferroptosis in ectopic endometrial stromal cells in patients with ovarian endometriosis could activate the p38 mitogen-activated protein kinase (p38 MAPK)/signal transducer and activator of transcription (STAT) 6 signalling pathway, thereby promoting local upregulation of vascular endothelial growth factor A (VEGFA) and interleukin-8 (IL-8) in ectopic lesions [ 15 ].…”
Section: Ferroptosis and Endometriosismentioning
confidence: 99%